2002
DOI: 10.4049/jimmunol.168.8.4209
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies Induce Monocyte Chemoattractant Protein-1 in Endothelial Cells

Abstract: The presence of antiphospholipid Ab is associated with increased risk of thrombosis. The monocyte-endothelial cell interaction has been suggested to play a key role at the site of vascular injury during thrombosis. Therefore, we tested the effect of anticardiolipin Abs (aCL) on the production of monocyte chemoattractant protein-1 (MCP-1) in HUVEC. We found that monoclonal aCL as well as IgG fractions from patients with antiphospholipid syndrome (APS-IgG) could induce the production of MCP-1 in HUVEC. The abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 55 publications
(30 reference statements)
3
28
0
1
Order By: Relevance
“…These findings confirmed and extended the observation that anti-cardiolipin IgG fractions activated EC in the presence of h2GPI [2]. Following these studies, other groups have confirmed this finding by using both polyclonal and monoclonal aPL [5][6][7][8]. Interestingly, aPL-mediated activation with ADM upregulation and pro-inflammatory cytokine secretion was also found with human brain and skin primary EC cultures, suggesting that such an effect might be generalized to EC from different anatomical sites [9].…”
supporting
confidence: 79%
See 1 more Smart Citation
“…These findings confirmed and extended the observation that anti-cardiolipin IgG fractions activated EC in the presence of h2GPI [2]. Following these studies, other groups have confirmed this finding by using both polyclonal and monoclonal aPL [5][6][7][8]. Interestingly, aPL-mediated activation with ADM upregulation and pro-inflammatory cytokine secretion was also found with human brain and skin primary EC cultures, suggesting that such an effect might be generalized to EC from different anatomical sites [9].…”
supporting
confidence: 79%
“…In fact, besides the interference with the eicosanoid metabolism and the induction of a proadhesive phenotype, in vitro EC incubation with aPL was reported to be able: (i) to up-regulate proinflammatory and chemokine synthesis and secretion [5][6][7][8], (ii) to modulate tissue factor (TF) expression on the cell membrane [10,11], (iii) to interfere with the protein C/S activation (review in Ref. [12]), (iv) to displace annexin V binding to the cell membrane [13], (v) to induce pre-pro-endothelin (ET)-I synthesis [14], (vi) to favour an apoptotic process [15,16] and (vii) to interact with late endosomes [17] (Table 1).…”
Section: The Pleiotropic Apl Effect On Endothelial Cellsmentioning
confidence: 99%
“…Endothelial cell activation might be induced by elevated circulating IgG levels among which specific IgGs and/or specific immune complexes might interact with the endothelium to activate endothelial cells inducing endothelial dysfunction. 37,38,39,40 Elevated endothelial permeability typical of endothelium dysfunction facilitates enhanced lipoprotein access, retention, and deposition in the intimal space, a classical feature of fatty streak formation. In this setting, the adhesion molecules and chemokines whose expression is upregulated in the aortas of gld3Ldl-r Ϫ/Ϫ mice are known to be key players in the recruitment of monocytes into the subendothelial space, thus favoring lesion progression.…”
Section: Discussionmentioning
confidence: 99%
“…3 APLAs, or antibodies to ␤2GP1, activate endothelial cells (ECs) leading to an increase in leukocyte adhesion molecule and tissue factor expression, chemokine and cytokine secretion, and monocyte adhesion. [4][5][6][7][8] Furthermore, APLAs activate monocytes and platelets, the latter in the presence of subactivating doses of thrombin. [9][10][11][12] The activation of these cells leads to inflammatory and procoagulant responses that may underlie the hypercoagulable state that characterizes APS.…”
mentioning
confidence: 99%